Local factors shaping public sector industrial relations in a context of crisis: A comparison of municipal administrations in Spain; Lokale Faktoren formen die Arbeitsbeziehungen des öffentlichen Sektors im Krisenkontext: Ein Vergleich spanischer Kommunalverwaltungen - Irene Ramos-Vielba; Richard Woolley (Industrielle Beziehungen, 2018)
The impact of the 2008 financial crisis led to the imposition of severe `crisis measures' focused on alleviating budget deficits at all levels of Spanish government. In this context, the central government sought to restrict regional and local government spending. One of the key mechanisms at the Spanish government's disposal was restricting public sector employment. This paper examines the responses to these centrally imposed measures in two local municipal governments, Bilbao (Basque Country) and Parla (Madrid) between 2010 and 2015. The paper applies a `varieties of capitalism' conceptual approach to investigate what it refers to as subnational institutional systems and suggests that processes of economic and social adjustment in Spain are also influenced by distinctive regional and local political economic arrangements. Key factors contributing to the different industrial relations outcomes observed in the two case study locations are described and discussed. The results show that different types and degrees of coordination can co-exist within a decentralised national political economy. – – Die Finanzkrise zog seit 2008 schwerwiegende ,,Krisenmaßnahmen“ nach sich, die auf allen Verwaltungsebenen Spaniens darauf konzentriert waren, das Haushaltsdefizit zu verringern. In diesem Kontext versuchte die Zentralregierung die Ausgaben regionaler und lokaler Verwaltungen zu beschränken. Eines der zentralen Instrumente über welche die spanische Regierung verfügte, war die Reduktion der öffentlichen Beschäftigung. Der Beitrag untersucht, wie die zwei Lokalverwaltungen von Bilbao (Baskenland) und Parla (Madrid) 2010 bis 2015 auf die zentral auferlegten Maßnahmen reagierten, indem ein Varieties of Capitalism-Konzept zur Untersuchung sub-nationaler Institutionen angewandt wird. Es wird der Schluss gezogen, dass Prozesse wirtschaftlicher und sozialer Anpassung in Spanien auch durch verschiedene regionale und lokale politische und wirtschaftliche Arrangements beeinflusst werden. Es werden Schlüsselfaktoren der unterschiedlichen Folgen für die industriellen Beziehungen beschrieben und diskutiert. Die Befunde zeigen, dass verschiedene Typen und Grade der Koordination innerhalb einer dezentralisierten Ökonomie existieren können.
Keywords: J45; J5; O52; 330; Spain; municipalities; public sector industrial relations; crisis management; Spanien; Kommunen; Arbeitsbeziehungen des öffentlichen Sektors; Krisenmanagement